2009
DOI: 10.1007/s00784-009-0335-8
|View full text |Cite
|
Sign up to set email alerts
|

Atraumatic restorative treatment versus amalgam restoration longevity: a systematic review

Abstract: (1) insufficient random or quasi-random allocation of study subjects; (2) not all entered subjects accounted for at trial conclusion; (3) subjects of both groups not followed up in the same way. Fourteen from the initial search of 164 articles complied with these criteria and were selected for review. From these, seven were rejected and seven articles reporting on 27 separate datasets, accepted. Only identified homogeneous datasets were combined for meta-analysis. From the 27 separate computable dichotomous da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
122
0
12

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(138 citation statements)
references
References 30 publications
4
122
0
12
Order By: Relevance
“…The success of ART restorations is dependent on several factors such as material, operator and technique 14 . The most common failures resulting from these factors are related to material wear, complete loss of the material and the associated decay on the edge of the cavity 12 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of ART restorations is dependent on several factors such as material, operator and technique 14 . The most common failures resulting from these factors are related to material wear, complete loss of the material and the associated decay on the edge of the cavity 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Specially designed for ART, the high-viscosity GICs have a relatively slow curing and improved mechanical properties compared to low and medium viscosity cements, which has resulted in increased survival of restorations 13 . Recent systematic reviews have shown that the longevity of ART restorations with high-viscosity GICs is similar to the gold standard treatment with amalgam 12,[14][15][16] .…”
Section: Introductionmentioning
confidence: 96%
“…Although some GIC restorations failed in obtaining a marginal adaptation at toothrestorations interface in this "in-vitro" setting, the material may have good performance in clinical situations due to fluoride release and uptake as well as the ability of delaying or preventing the development of secondary caries lesions [7]. Notwithstanding clinical studies must be performed to assess this condition in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Sometimes the severity of those diseases requires restorative treatment in order to bring back functionality and esthetic [4,5]. Glass Ionomer Cements (GIC) are elective materials for restorations in such kind of dental problems because they have excellent properties such as fluoride release and uptake and biocompatibility [6][7][8] Thanks to its sustained benefits is now used in daily clinical settings and all kind of populations [9].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the effectiveness of ART [6][7][8][9] associated with reduced clinical time and cost, make this approach a promising option for the Brazilian public health system, that may aid to reduce inequalities. Thus, the use of ART could assist in achieving the public health system goals, which are to improve access and health levels, and to reduce the impact of treatment costs [10].…”
Section: Introductionmentioning
confidence: 99%